ANALISIS TINGKAT KEPUASAN PENGGUNA WEBSITE LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (LAPOR) PADA DISKOMINFO-SP PEMKAB BANYUASIN MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Eka Puji Agustini; Ahkam Gagah Wahyudi (P3M Institut Teknologi Pagar Alam, 2023)
The people's online aspiration and complaint service (LAPOR) is a complaint system established by the government as a form of commitment in supporting the principle of open government and improving the quality of public services. This study aims to determine and analyze the level of user satisfaction of the people's aspiration and online complaint service website (LAPOR) at Diskominfo-Sp of the banyuasin district government using the end user computing statisfaction (EUCS) method, which is a method used to measure the level of satisfaction of users of a website / application system by comparing expectations and reality of an information system, In this study, 5 EUCS indicators were measured which will determine the level of satisfaction of LAPOR website users, namely Content, Accuracy, Format, Ease to Use, and Timeliness. This research uses a quantitative research design by conducting surveys and questionnaires as research instruments. with a sample size of 100 people. The data analysis technique used with the multiple linear regression analysis approach. The sampling technique used in this study is probability sampling with simple random sampling technique (random sampling sample). The results of data analysis show content (X1), accuracy (X2), format (X3), ease of use (X4), and timeliness (X5) on user satisfaction (Y), it is stated that there are 4 variables that have a significant effect, namely the content variable (X1), accuracy (X2), format (X3), and ease of use (X4). There is 1 variable that is declared to have no effect on user satisfaction, namely the timeliness variable (X5) and From the results of the F test, the results of the analysis of the content (X1), accuracy (X2), format (X3), ease of use (X4), and timeliness (X5) variables on user satisfaction (Y) show that there is a simultaneous influence and significance on user satisfaction on the LAPOR! DISKOMINFO-SP Banyuasin Regency Government.